Cultivating studentsâ environmental awareness by creating bottle garden in school: A qualitative study - Situmorang, Risya Pramana; Tarigan, Sari Dewi (Jurnal Pendidikan Biologi Indonesia, 2018)
Environmental awareness has becoming a critical value to be integrated among youth. This research aimed to analyze the implementation of studentsâ environmental awareness of Christian Junior High School 2 in Salatiga by creating bottle garden in school. This research was descriptive qualitative which was conducted in the second semester of academic year 2017/2018 and involved 47 students. The data collection techniques used were questionnaire and observation. The implementation of environmental awareness was measured based on the New Ecological Paradigm theory with five main indicators, namely: 1) anti-exemptionalism, 2) anti-anthropocentrism, 3) limits to growth, 4) balance of nature, and 5) eco-crisis. The results showed that by learning through bottle garden activities, students have reached a good understanding of eco-crisis, anti-exemptialism, balance of nature, anti-anthropocentrism, and limit of growth in which the value were 3.35; 3.11; 3.2; 3.19; and 3.14 respectively (3.21 â¤ score <3.73). This means that the students have possessed a âgoodâ level of environmental awareness.